Selling a presidential candidate: linguistic landscapes in time of presidential elections in Zambia. Issue 2 (15th March 2021) - Jimaima, Hambaba; Banda, Felix
ABSTRACT: We use a moment in history, the lead up to presidential elections, to capture the semiotic transformation of linguistic landscapes of a multilingual African country, Zambia. We use observations and notions of assembling artefacts and semiotic assemblages to show that the semiotic product resulting from the rallies and campaign material from three selected political parties is not just made up of displays of party colours, slogans, song, dance, unique symbols, gestures and multilingual discourses; the assemblage of images of human ethno-types in campaign materials and at rallies as body semiotics, are critical to party brand identification and the selling of presidential candidates. Considering that Zambia has more than 72 ethnic groups scattered in 10 provinces, we analyse the strategies the parties adopt to avoid the liability of being seen as regional and ethnically based. We conclude that selling of a presidential candidate involves deployment of contradictory logics of de-ethnicisation, de-emphasising the presidential candidate's ethnic background, and ethnicisation, a careful framing of political parties and rallies and campaign material as sites of multilingual, multi-ethnic and trans-region spatial practices.